Aplikasi Konsep Nebula pada Klub Malam dan Bar di Balikpapan - Beatrice Ismed Alimin; Stephanus P Honggowidjaja; purnama esa dora tedjokoesomo (Intra, 2014)
An interior design "Night Clubs and Bars in Balikpapan"has becomes a night entertainment facility atlernative for the middle and upper class, particularly the young executives. A Place that help balancing between work and relaxation for every individual who comes, provided with facilities such as good service, music that can be enjoyed by everyone, also the security is well maintained, as well as a satisfaying beautiful viewof the city. The nightclub is divided into three areas for visitors, i.e. lobby, bar area, and dance area. With stages that go into space. Space is provided as follows; lobby, bar with seating area, entertainment area, up to the dance area in accordance with the concept of "Nebula".